THE IMPLEMENTATION OF PSAK 69 IN THE LIVESTOCK SUB-SECTOR COMPANIES - Nurul Hasanah Uswati Dewi; Yasmine Firdaus; Gunasti Hudiwinarsih; Nosy Yodi Metana (Jurnal Bisnis dan Akuntansi, 2024)
This study was conducted to explore how the implementation of accounting standard in agriculture sector companies in the livestock sub-sector in Indonesia. The data collection method used documentation techniques which were then analyzed using the Miles and Huberman model. The results show that all research subjects have been recognized and measured in accordance with accounting standard for asset agriculture and some have made full disclosure points based on accounting standard.  The number of samples from livestock companies is limited and difficult to obtain or access because not many companies in this sector are open to the public, most are still dominated by family-owned companies, local companies to MSMEs and some livestock companies are non-publicly or private companies This research is able to become an evaluation and recommendation for livestock companies to be encouraged to implement accounting standard in their financial reporting, in order to provide relevant information for investors.